the effectiveness of the differentiated education strategy in teaching mathematical concepts to educationally retarded pupilsin the first-grade school - gozim, Mohamed; Hermez, Djamila (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
The study aimed to identify the effectiveness of the differentiated education strategy in teaching mathematical concepts to educationally retarded pupilsin the first grade school at Tahiri Belkheir Middle School in Messaad (Algeria). To achieve the study objectives, we designed the study tools represented in a test of mathematical concepts, which consisted of (20) items in the unit of relative numbers and integrated guide for the use of the differentiated education strategy in teaching. We also selected a purposive sample of educationally retarded pupils, made up of (36) pupils. We used the experimental method and the sample was divided into two groups (experimental and control). The experimental group was studied using a differentiated education strategy, as it consisted of (19) students with an average age of (12.6 years). The number of the control group is (17) students, with an average age (12.2 years), was taught in the traditional method of teaching. The results of the study showed that there are statistically significant differences between the average scores of educationally retarded pupils for two groups: control group who studied using the traditional teaching method and the experimental one using the differentiated education strategy in the test of mathematical concepts, in favor of the experimental group. In light of the results of the study, the researcher put forward several recommendations and proposals directed to the educators and researchers in the field of psychology, the most important of which is the inclusion of the differentiated education strategy in the educational curriculum guide.